1998
DOI: 10.1002/(sici)1099-1581(1998100)9:10/11<672::aid-pat848>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity in ferroelectric liquid crystalline elastomers

Abstract: The direct and inverse piezoelectricity in single crystal ferroelectric liquid crystalline elastomers was measured by means of purpose-made experimental setups. As expected the observed effects depended strongly on temperature and the strength of the applied alternating electric field; additionally they could be strongly enhanced by a superimposed direct current electric field. The latter resulted from a molecular amplification of the polarization vector of the single smectic layers by inducing a rotational bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Since the first introduction of SCLC polymers by Finkelmann and coworkers in 1978,3, 4 there have been many studies of the effects of the molecular structures of the polymer backbones, spacer groups, and mesogenic side chains on the thermal and physical properties of these polymers 5–10. Furthermore, many studies have been reported on the applications of such polymers in areas such as ferroelectric display devices,1, 11–13 nonlinear optics,14–17 optical storage data,18 pyroelectric detectors,19 and artificial muscles 1, 20, 21…”
Section: Introductionmentioning
confidence: 99%
“…Since the first introduction of SCLC polymers by Finkelmann and coworkers in 1978,3, 4 there have been many studies of the effects of the molecular structures of the polymer backbones, spacer groups, and mesogenic side chains on the thermal and physical properties of these polymers 5–10. Furthermore, many studies have been reported on the applications of such polymers in areas such as ferroelectric display devices,1, 11–13 nonlinear optics,14–17 optical storage data,18 pyroelectric detectors,19 and artificial muscles 1, 20, 21…”
Section: Introductionmentioning
confidence: 99%
“…This problem can be overcome by using ferroelectric LC gels. 66,69,[71][72][73][74] Fig. 17 illustrates the creation of a monodomain in a ferroelectric LC elastomer.…”
Section: Memory Effects Of Lc Networkmentioning
confidence: 99%
“…This enables to analyse in detail the reorientation of the single molecular moieties in the supramolecular system (angle of reorientation, time constant, phase relationship) in response to an external electric field. To measure the (inverse) piezoelectric effect interferometric and x-ray methods are used [4,5]. It is discovered that FLCE in a proper crosslinking density show the highest electrostrictive coefficients which were found up to now for any material.…”
Section: Universität Leipzig Germanymentioning
confidence: 99%
“…It is discovered that FLCE in a proper crosslinking density show the highest electrostrictive coefficients which were found up to now for any material. A microscopic interpretation of the observed marcoscopic effects will be presented [5,6].…”
Section: Universität Leipzig Germanymentioning
confidence: 99%
See 1 more Smart Citation